Diarrhoea in young dairy calves. Issue 1 (10th January 2013) - Baxter, Keith
ABSTRACT: An outbreak of diarrhoea occurred in a spring calving herd in Hampshire, during February–March 2011. Mortality of young calves, and subsequent disease in older calves, was significant. After reviewing and improving management of the situation in the very young calves, there was a subsequent problem with calves at 3–4 weeks of age, which was resolved with group antibiotic treatment.